The Utilization of Waste as Iron Ore in Making Concrete Aggregate Quality K.300 - Rajiman Rajiman; Muhamad Amin; Harjianto Setiaji (Rekayasa Sipil, 2020)
Concrete is an manmade building material that looks like stone. Concrete is a composite material consisting of coarse-grained material (aggregates or fillers) that is embedded in a solid matrix of material (cement or binder) that fills the space between the aggregate particles and glues them together. Concrete is used for road hardening, building structures, foundations, roads, bridges and the basis for fences.The method used in this research is study of literature. This research found that concrete using iron ore as an aggregate has a compressive strength higher than normal concrete that is equal to 38.90Mpa assuming greater size of iron ore as aggregate, the higher the Fe content, the size of escaped iron ore mesh aggregate 20, mesh 20 , mesh 5, 8-10 mesh and 10-12 mm mesh respectively 47,460%, 38,346%, 49,330%, 58,660% and 69,225%.